The effects of furosemide on kidney damage in acute kidney injury rat models - Afifah Afifah; . Ngatidjan; Nur Arfian (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
The most frequent cause of acute kidney injury (AKI) is ischemia reperfusion injuriesthat causes inflammation. Furosemide is still used in AKI’s therapy. The advantages anddisadvantages of furosemide in AKI remain controversial. The aim of the study was toinvestigate the effect of furosemide on kidney damage in AKI rat models. Twenty-fivemale (2-3 months old) Sprague-Dawley rats were divided into 5 groups; sham operation(SO, n=5), ischemic-reperfusion (IR, n=5), IR+furosemide 3.6 mg/kgBW (IR+F1,n=5), IR+furosemide 7.2 mg/kgBW (IR+F2, n=5), and IR+furosemide 14.4 mg/kgBW(IR+F3, n=5). Abdominal surgery was performed under ketamine anesthesia to produceischemic reperfusion (IR) by mean of renal artery clamping for 45 min. Urine output,serum creatinine level, tubular injury score, and TLR4 gene expression were examinedto investigate kidney damage. Periodic acid-schiff (PAS) staining was measured toexamine kidney tubular injury. Data were analyzed using One-Way ANOVA and Kruskal-Wallis test with significance level of p<0.05. AKI rat models which were given 3.6 and7.2 mg/kgBW of furosemide (0.014±0.001 mL/min; and 0.012±0.007) showed higher(p>0.05) creatinine clearance compared to IR (0.009±0.003) while administration of 14.4mg/kgBW furosemide (0.009±0.004) denoted equal creatinine clearance to IR (p>0,05).Kidney tubular injury score of 3.6 mg/kgBW furosemide (2.89±0.13) was lower (p>0.05)than IR (3.26±0.19) whereas 7.2 mg/kgBW and 14.4 mg/kgBW furosemide (3.55±0.26;3.83±0.19) were higher (p<0.05) than IR. Administration of 3.6 mg/kgBW furosemide(0.99±0.08) indicated lower (p<0.05) TLR4 gene expression than IR (1.20±0.08) whilst7.2 mg/kgBW furosemide (1.23±0.13) was not-significantly higher (p>0.05) and 14.4 mg/kgBW furosemide (1.63±0.12) was significantly higher (p<0.05) than IR. In conclusion,administration of 3.6 mg/kgBW furosemide reduces kidney damage in AKI rat modelswhile higher dosages (7.2 mg/kgBW and 14.4 mg/kgBW) increase kidney damage.